Saccharide orientation at the cell surface affects glycolipid receptor function. - Strömberg, N (1991)
Three allelic variants of P-pilus-associated G-adhesins (lectins) with different cell-binding properties were recently described. Here we have analyzed Escherichia coli HB101 strains expressing the recombinant G-adhesin variants for their ability to agglutinate erythrocytes from various species as this relates to the glycosphingolipid (GSL) composition in the erythrocyte membranes. All three variants exhibit similar specificities for the globo-series GSLs affixed to artificial surfaces. However, only the PapGJ96 adhesin induces agglutination of erythrocytes having globotriaosylceramide (GbO3) [Gal(alpha 1-4)LacCer] as the major GSL. Furthermore, only PapGAD110 induces strong agglutination of erythrocytes having globotetraosylceramide (GbO4) [GalNAc(beta 1-3)Gal(alpha 1-4)LacCer] as the major GSL, while PrsGJ96 alone agglutinates those containing globopentaosylceramide (GbO5) [GalNAc(alpha 1-3)GalNAc(beta 1-3)Gal(alpha 1-4)LacCer]. Molecular modeling of these globo-GSLs demonstrates different saccharide orientations to the membrane surface for these isoreceptors. We suggest that the differential binding of the three G-adhesin variants results from differences in epitope presentation at the membrane among these globo-GSLs.